1997
DOI: 10.1073/pnas.94.2.757
|View full text |Cite
|
Sign up to set email alerts
|

Failure to express the P-selectin gene or P-selectin blockade confers early pulmonary protection after lung ischemia or transplantation

Abstract: Endothelial P-selectin expression contributes to the first wave of neutrophil (polymorphonuclear leukocyte; PMN) inf lux in several inf lammatory conditions. Although remote tissue ischemia, such as a crush injury to the hindlimb, may result in P-selectin-mediated pulmonary leukosequestration, it is not known whether the lungs exhibit a similar response after hypothermic preservation or when subjected to a direct ischemic insult. To determine if P-selectin may mediate early primary graft failure, left lungs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 41 publications
0
48
0
Order By: Relevance
“…Blockade of both leukocyte integrin adhesion molecule and its counterpart, intercellular adhesion molecule-1 (ICAM-1), has been shown to be efficient in a rat lung transplant model, as combined administration of monoclonal antibodies against ICAM-1, CD11a and CD18 resulted in superior gas exchange 24 h after reperfusion and reduced neutrophil accumulation in lung tissue [20]. In addition, blockade of P-selectin by a monoclonal anti-P-selectin antibody or a selectin inhibitor improved graft function and reduced PMN infiltration after syngeneic rat lung transplantation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of both leukocyte integrin adhesion molecule and its counterpart, intercellular adhesion molecule-1 (ICAM-1), has been shown to be efficient in a rat lung transplant model, as combined administration of monoclonal antibodies against ICAM-1, CD11a and CD18 resulted in superior gas exchange 24 h after reperfusion and reduced neutrophil accumulation in lung tissue [20]. In addition, blockade of P-selectin by a monoclonal anti-P-selectin antibody or a selectin inhibitor improved graft function and reduced PMN infiltration after syngeneic rat lung transplantation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence against this role includes findings that P-selectin-inhibitory mAb does not block leukocyte rolling in venules (26) and that bacteria-induced leukocyte migration is not inhibited in P/E-selectin-knockout mice (27). Evidence supporting a role for P-selectin includes findings that P-selectin-blocking mAbs inhibit ALI induced by cobra venom (28) or ischemia-reperfusion (29) and that P-selectin-knockout mice are protected from ALI due to ischemia-reperfusion (30). We reported that P-selectin accounts for the pressure-induced leukocyte accumulation (6), thereby implying a role for P-selectin in the proinflammatory phenotype induced by pulmonary venous hypertension.…”
Section: Mitochondrial Buffering It Is Proposed That Mitochondria Bumentioning
confidence: 99%
“…Ischemia-reperfusion injury increases activation of vascular endothelial cells and releases a variety of chemoattractants, which help the activated neutrophils influx into the lung parenchyma with the coordination of adhesion molecules that are upregulated during ischemia-reperfusion injury (5). During this nonspecific insult, it has been thought that neutrophils play a key role through a number of mechanisms including release of reactive oxygen species and proteolytic enzymes (6).…”
Section: Introductionmentioning
confidence: 99%